Disability and the way of Jesus : holistic healing in the Gospels and the church - Fox, Bethany McKinney, 1977-; Swinton, John (Downers Grove : IVP, an imprint of InterVarsity Press, 2019)
What does healing mean for people with disabilities? Bridging biblical studies, ethics, and disability studies with the work of practitioners, Bethany McKinney Fox examines healing narratives in their biblical and cultural contexts. This theologically grounded and winsomely practical resource helps us more fully understand what Jesus does as he heals and how he points the way for relationships with people with disabilities.
Bridging the gap -- The first century context of Jesus the healer -- Physicians interpret the Gospels' healing narratives -- Honoring the lived experience of disability in the Gospel healing narratives -- Pastors discuss their churches' healing practices and the healing activity of Jesus -- The seven marks of healing in the way of Jesus -- The seven marks of healing in action.
Includes bibliographical references and indexes.
Description based on online resource; title from digital title page (viewed on March 27, 2020).
Master record variable field(s) change: 050
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Healing in the Bible; Healing -- Biblical teaching; Healing -- Religious aspects -- Christianity; Disabilities -- Religious aspects -- Christianity; Disabilities -- Biblical teaching; RELIGION -- Christian Life -- General; RELIGION -- Christian Ministry -- Adult; RELIGION -- Christian Ministry -- Counseling & Recovery; Disabilities -- Religious aspects -- Christianity; Healing -- Biblical teaching; Healing in the Bible; Healing -- Religious aspects -- Christianity; Electronic books; Criticism, interpretation, etc